2019
DOI: 10.22434/ifamr2019.0030
|View full text |Cite
|
Sign up to set email alerts
|

Thinking beyond collateral in value chain lending: access to bank credit for smallholder Vietnamese bamboo and cinnamon farmers

Abstract: Using case studies of the bamboo and cinnamon value chains in rural areas of northern Vietnam, this paper contributes to the existing literature by analyzing barriers and suggests conditions under which value chain lending would be an effective tool for improving smallholder farmers’ access to credit. A mixed method using both in-depth interviews with relevant stakeholders and a two-stage Heckman model is employed to explain the existing credit gap. Findings show that in both chains, bank decision-making on le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…This result is consistent with Chandio et al (2020), who found that formal credit demand was positively affected by landholding. Banks prefer lending credits to borrowers with an account with them so that they can better monitor their cash flows (Luan and Kingsbury, 2019). This finding is consistent with Dzadze et al (2012), who reported a positive relationship between possession of savings accounts and access to formal credit by farmers.…”
Section: Effect Of Avc Participation On Farmers' Credit Accesssupporting
confidence: 84%
See 4 more Smart Citations
“…This result is consistent with Chandio et al (2020), who found that formal credit demand was positively affected by landholding. Banks prefer lending credits to borrowers with an account with them so that they can better monitor their cash flows (Luan and Kingsbury, 2019). This finding is consistent with Dzadze et al (2012), who reported a positive relationship between possession of savings accounts and access to formal credit by farmers.…”
Section: Effect Of Avc Participation On Farmers' Credit Accesssupporting
confidence: 84%
“…Lenders' criteria for advancing credit are mainly tied to the educational level, nature (size) of the farm business, cash flow, account turnovers, familiarity with the potential borrower and how the loan affects farmers' outputs, among others. The approach does not consider contractual arrangements between farmers and off-takers to buy farm produce, which negatively affects farmers' loan repayment (Köhn, 2014; Luan and Kingsbury, 2019).…”
Section: Agricultural Financing In Ghana: Trends Problems and Empiricsmentioning
confidence: 99%
See 3 more Smart Citations